Effect of OATP1B1 genotypes on plasma concentrations of endogenous OATP1B1 substrates and drugs, and their association in healthy volunteers - Mori, Daiki; Kashihara, Yushi; Yoshikado, Takashi; Kimura, Miyuki; Hirota, Takeshi; Matsuki, Shunji; Maeda, Kazuya; Irie, Shin; Ieiri, Ichiro; Sugiyama, Yuichi; Kusuhara, Hiroyuki (Drug metabolism and pharmacokinetics, 2019)
This study aimed to elucidate the impact of OATP1B1 genotype (*1b/*1b, *1b/*15, and *15/*15) on plasma concentrations of endogenous OATP1B1 substrates. Healthy volunteers with OATP1B1 *1b/*1b (n = 10), *1b/*15 (n = 7), or *15/*15 (n = 2) received oral administration of a cocktail of statins (atorvastatin, pitavastatin, rosuvastatin, and fluvastatin). Mean area under the plasma concentration of atorvastatin, pitavastatin, and rosuvastatin in OATP1B1 *15/*15 were 2.2, 1.7 and 1.58-times greater than the corresponding values in OATP1B1 *1b/*1b, respectively, whereas that of fluvastatin was identical to those in other OATP1B1 genotypes. OATP1B1 *15/*15 also showed higher mean plasma concentrations of OATP1B1 endogenous substrates compared with the other OATP1B1 genotypes, such as coproporphyrin I, glycochenodeoxycholate sulfate (GCDCA-S), lithocholate sulfate (LCA-S), glycolithocholate sulfate (GLCA-S) and taurolithocholate sulfate (TLCA-S), but not total or direct bilirubin, chenodeoxycholate-24-glucuronide, or ω-dicarboxylic long-chain fatty acids. Area under the plasma concentration-time curves of plasma coproporphyrin I and GLCA-S discriminated OATP1B1 genotype *15/*15 from the other genotypes. In combination with previously published clinical studies, these results support the notion that coproporphyrin I, and GLCA-S and GCDCA-S could be a surrogate probe for assessing human in vivo OATP1B1 activities. [Display omitted]